Ungoverned Spaces and Alternative Sovereignties in Nigeria: Terror Groups, National Security and Sustainable Development - Sackflame, Mary Magdalene; Omitola, Bolaji (Faculty of Law Universitas Negeri Semarang, 2022)
Nigeria is currently battling with threats that are potent enough to undermine its existence as a sovereign polity. These terrors are coming mostly from groups occupying and controlling diverse ungoverned spaces that littered the country’s landscape. From Boko Haram insurgents, Bandits, herdsmen to ethnic militias; these groups are becoming laws unto themselves and creating spheres of influence and jurisdictions due to government and state apparatus absence. This article examines the conditions that created ungoverned spaces, the activities of diverse groups inhabiting them and the implications on national security and sustainable development. The article adopts qualitative method and relies on secondary data sourced from newspapers, government documents, internet resources and extant scholarly works. The article findings reveal that achievement of the sustainable development goals 1-No Poverty, 2- Zero Hunger, 3-Good Health and Well-being, 4-Quality Education, 6-Clean Water and Sanitation, 8- The interrelatedness of the Sustainable Development Goals and 16- Peace, Justice and Strong Institution are seriously hindered as far as the atmosphere and conditions for peaceful co-existence becomes elusive as various groups continue to contest sovereignty with the Nigerian state. Conclusively therefore, it is recommended that a sustainable national security strategy to ensure peace and reduce conflicts through government presence in the various ungoverned spaces must be pursued.